Analysis of high power microwave induced degradation and damage effects in AlGaAs/InGaAs pHEMTs. Issue 8 (July 2015) - Yu, Xinhai; Chai, Changchun; Liu, Yang; Yang, Yintang; Fan, Qingyang
Highlights: High power microwave (HPM) induced damage mechanism in pHEMT. HPM induced gate metal diffusion results in DC/RF performance degradation. RF performance deterioration is utilized as the degradation (or damage) criteria. HPM induced failure of LNA is attributed to the failure of the first stage pHEMT. Physical evidences are revealed through SEM to validate the mechanisms analysis. Abstract: The high power microwave (HPM) induced effects in AlGaAs/InGaAs pseudomorphic high electron mobility transistors (pHEMTs) are investigated by simulation and experiments. Simulated results suggest that the HPM damage mechanism is device burnout, which is caused by emerging current path and strong electric field intensity beneath the gate metal. Besides, analysis points out that the gate metal diffusion may be thermally activated, resulting in DC and RF performance degradation. Specifically, a positive shift will occur to the pinch-off voltage while accordingly the small-signal gain will decrease. The HPM injection experiments on the dual-stage pHEMT low noise amplifiers (LNAs) are carried out. Experimental results substantiate that deterioration happens both in the noise figure and in the small-signal gain, which is in agreement with the simulated results. Failure analysis indicates that the HPM induced failure of LNA is attributed to the failure of the first stage pHEMT. Finally, samples dissection analysis using the scanning electron microscopy (SEM) verifies the simulation analysis of the damage mechanism and the location susceptible to burnout. Meanwhile, the assumption of gate metal diffusion is validated by the observation of pits after removing the gate metal. The performance parameters deterioration can be utilized as the degradation (or damage) criteria, and the mechanisms analysis facilitates making reinforcing design.